The ADA (Age-D-Dimer-Albumin) Score to Predict Thrombosis in SARS-CoV-2 - Violi, Francesco; Pignatelli, Pasquale; Vestri, Anna Rita; Spagnoli, Alessandra; Cipollone, Francesco; Ceccarelli, Giancarlo; Oliva, Alessandra; Amitrano, Maria; Pirro, Matteo; Taliani, Gloria; Cangemi, Roberto; Lichtner, Miriam; Pugliese, Francesco; Falcone, Marco; D'Ardes, Damiano; Venditti, Mario; Mastroianni, Claudio Maria; Loffredo, Lorenzo; the ADA GROUP; D'Agostino, Fausto; Agrò, Felice Eugenio; Mattei, Alessia; Tibullo, Loredana; Nunziata, Maria Grazia; Iorio, Valeria; Iuliano, Natalia; Mangiacapra, Sara; Raimondo, Mariangela; Atteno, Mariangela; Ferri, Claudio; Grassi, Davide; Desideri, Giovambattista; Abballe, Stefano; Dell'Isola, Serena; Rocco, Monica; Alampi, Daniela; Borgo, Cosmo Del; Bianconi, Vanessa; Mannarino, Massimo Raffaele; Figorilli, Filippo; Maggio, Enrico; Fino, Pasquale (Thrombosis and Haemostasis, 2022)
Background Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-related pneumonia is associated with venous and arterial thrombosis. Aim of the study was to find out a new score for predicting thrombosis in patients with SARS-CoV-2.Methods We included a cohort of 674 patients affected by SARS-CoV-2, not requiring intensive care units, and followed-up during the hospitalization until discharge. Routine analyses performed at in-hospital admission included also serum albumin and D-dimer while arterial and venous thromboses were the endpoints of the study.Results During the follow-up, 110 thrombotic events were registered; patients with thrombotic events were older and had lower albumin and higher D-dimer, compared with thrombotic event-free ones. On multivariable logistic regression with step-by-step procedure age, serum albumin, and D-dimer were independently associated with thrombotic events. The linear combination of age, D-dimer, and albumin allowed to build-up the ADA (age-D-dimer-albumin) score, whose area under the curve (AUC) was 0.752 (95% confidence interval [CI], 0.708–0.795). ADA score was internally validated by bootstrap sampling procedure giving an AUC of 0.752 (95% CI: 0.708–0.794).Conclusion Combination of age, D-dimer, and albumin in the ADA score allows identifying SARS-CoV-2 patients at higher risk of thrombotic events.
Keywords: venous thrombosis; viral infection; thrombosis